2015
DOI: 10.1097/hnp.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spiritual Needs and Practices of Oncology Patients in Turkey

Abstract: The purpose of this study was to assess the oncology patients' spiritual needs and activities. Besides, the study was to provide clinical evaluation of the feasibility and usefulness of the Patients Spiritual Needs Assessment Scale. This descriptive and cross-sectional study was performed by using a demographic and spiritual practices questionnaire, the Turkish version of the Patients Spiritual Needs Assessment Scale. The results of our study demonstrated that the most common spiritual needs of patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 14 publications
5
59
0
6
Order By: Relevance
“…The response categories were "never," "rarely," "fairly often," and "very often." The Turkish version of the SNAS were tested by Dedeli et al 9 Cronbach' alpha for the Turkish version of the SNAS was 0.89.The scale are well-documented, and norm values for a Turkish population are available. (9) In the present study, alpha coefficient was found 0.87 for the SNAS.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The response categories were "never," "rarely," "fairly often," and "very often." The Turkish version of the SNAS were tested by Dedeli et al 9 Cronbach' alpha for the Turkish version of the SNAS was 0.89.The scale are well-documented, and norm values for a Turkish population are available. (9) In the present study, alpha coefficient was found 0.87 for the SNAS.…”
Section: Methodsmentioning
confidence: 99%
“…Family members would stay by the bedside reciting the Holy Quran (Koran) hoping to imbue peace and serenity into the heart of the loved one. (9,13,15) Spirituality is a distinctive, potentially creative and universal dimension, rising both within the inner subjective awareness of individuals and within communities. Several studies demonstrated that many individuals rely on their spirituality and faith when coping with stres in most cultures.…”
Section: Dıscussıonmentioning
confidence: 99%
See 3 more Smart Citations